Growth Inhibition of Various Enterobacteriaceae Species by the Yeast Hansenula anomala during Storage of Moist Cereal Grain - Olstorpe, Matilda (American Society for Microbiology, 2012)
Eleven of 13 Enterobacteriaceae species tested grew in moist stored wheat, highlighting a potential risk of this energy-saving airtight storage method. When Hansenula anomala was coinoculated, all Enterobacteriaceae species were significantly inhibited after 2 months of storage, six of them to below the detection limit.